Optimization for Upgradation of Small Hydropower Plant in Nepal: A Case Study of Sundarijal Hydropower Plant - Raut, Prahlad; Shrestha, Rajendra; Gautam, Pashupati Raj (Journal of the Institute of Engineering, 2018)
Efficiencies of electro-mechanical components of the Sundarijal Hydropower Plant in Nepal has been decreased and the plant has been generating less energy than design generation. The study shows that the plant can be upgraded to 1.1 MW capacity at Q60 design with rehabilitation. Main objective of the plant rehabilitation is to improve operational stability and reliability of power supply by increasing capacity, efficiency, and safety of the plant. The research is based on the Residual Life Assessment of hydro-mechanical components. Minimum thickness of existing penstock obtained from measurement is six mm which is sufficient for upgradation at Q60 design. Mechanical and chemical properties of penstock is found to be acceptable for upgradation. Machine foundations are tested to be safe for upgradation. Upgradation can be carried out for two scenarios: i) using two generating units system ii) using three generating units system. Energy generation per annum from two generating units system is 65.92 MWh lower than three generating units system. The difference in annual revenue between two systems is 3.93 thousand USD. Capital cost estimation shows that cost for three generating three generating units system is higher than two generating units system by 152 thousands USD. Cash flow analysis shows that IRR ratio for two generating units system is higher than three generating units system by three percentage. Upgradation with two generating units system is more suitable and beneficial than three generating units system. Optimization of turbine units is also carried out using nonlinear gradient reduction method in excel solver. Journal of the Institute of Engineering, 2018, 14(1): 82-95